PLURALISTIC EXTENSION EDUCATION METHODOLOGIES FOR EFFECTIVE TECHNOLOGY APPLICATION: A CASE OF POTATO TECHNOLOGIES IN INDIA - dubey, shantanu kumar; Sah, Uma; Pamdey, N K; Kokate, K D; Singh, Atar (Potato Journal, 2021)
This paper synthesizes the retrospective studies done by the frontline extension systems across three agroecologicalzones (AEZs) of potato cultivating regions in India viz., north-eastern region, north western hills and centralplain zones. The issues across these AEZs have been delineated. Accordingly, the on-farm research done to address mostprioritized problems across these three AEZs has been synthesized in order to emanate the different models of technologyapplication. The findings of the empirical synthesis showed that there were combinations of models of technologydissemination apropos the agro-ecological zones. Likewise, the efforts made by the main (field) extension systems werealso documented for large-scale spread of potato production technologies.